The Effects of a 785-nm AlGaInP Laser on the Regeneration of Rat Anterior Tibialis Muscle After Surgically-Induced Injury - Cressoni, Marcela Dalla Costa; Khalil Dib Giusti, Helena Hanna; Casarotto, Raquel Aparecida; Anaruma, Carlos Alberto [UNESP] (Mary Ann Liebert, Inc., 2008)
Objective: This study aims to investigate the effects of low-level laser therapy (LLLT) on muscle regeneration. For this purpose, the anterior tibialis muscle of 48 male Wistar rats received AlGaInP laser treatment (785 nm) after surgically-induced injury.Background Data: Few studies have been conducted on the effects of LLLT on muscle regeneration at different irradiation doses.Materials and Methods: The animals were randomized into four groups: uninjured rats (UN); uninjured and laser-irradiated rats (ULI); injured rats (IN); and injured and laser-irradiated rats (ILI). The direct contact laser treatment was started 24 h after surgery. An AlGaInP diode laser emitting 75 mW of continuous power at 785 nm was used for irradiation. The laser probe was placed at three treatment points to deliver 0.9 J per point, for a total dose of 2.7 J per treatment session. The animals were euthanized after treatment sessions 1, 2, and 4. Mounted sections were stained with hematoxylin and eosin and used for quantitative morphological analysis, in which the number of leukocytes and fibroblasts were counted over an area of 4480 mu m(2). The data were statistically analyzed by analysis of variance (ANOVA) and the Bonferroni t-test.Results: Quantitative data showed that the number of both polymorphonuclear and mononuclear leukocytes in the inflammatory infiltrate at the injury site was smaller in the ILI(1), ILI(2), and ILI(4) subgroups compared with their respective control subgroups (IN(1), IN(2), and IN(4)) for sessions 1, 2, and 4, respectively (p < 0.05). on the other hand, the number of fibroblasts increased after the fourth treatment session (p < 0.05). With regard to the regeneration of muscle fibers following injury, only after the fourth treatment session was it possible to find muscle precursor cells such as myoblasts and some myotubes in the ILI(4) subgroup.Conclusion: During the acute inflammatory phase, the AlGaInP laser treatment was found to have anti-inflammatory effects, reducing the number of leukocytes at the injury site and accelerating the regeneration of connective tissue.